The study of the Persian mystical fable's capacity to be rewritten as spiritual literature for children in the light of the theory of relational consciousness. Issue 1 (2nd January 2019) - Qayyoumi, Samira; Jalaeifar, Zahra
ABSTRACT: 'Relational consciousness' introduces four kinds of relationships as characteristics of children's spirituality: relation with self, others, environment and the higher being or God. These four relationships have also been noted in Persian mystical fables. The aim of the present study is to review some of these fables so as to assess their capacity for being rewritten as spiritual literature for children in the light of this theory. We contend that fables which pay more attention to the relationship with self and God, have less capacity because of their abstract concepts. Fables concerning the relationship with the environment and others are more suitable for being rewritten for the child reader, as they are more objective and perceptible. Many fables of this kind have the potential to guide the reader from the relationship with the environment and others to the relationship with self and God. The study also shows that Persian mystical fables could be used as a rich source for nourishing the child's spirituality according to the theory of relational consciousness.